Toponyms in Karakalpak Dastans Formed from Somatisms (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In the article issues related to the occurrence of body parts names in onomastics, mainly toponymy, are studied on the example of toponyms found in Karakalpak epics. Concepts are given on the use and meaning of the names of body parts such as bawır (liver), búyrek (kidney), bel (waist), moyın (neck), qoltıq (armpit),qol (hand), kindik (umbilicus),  taban (foot), murın (nose), qan (blood) in naming geographical objects. The geographical meanings of body terms in Turkic languages have been studied.